A comprehensive analysis identifies BRAF hotspot mutations associated with gliomas with peculiar epithelial morphology. Issue 3 (28th October 2016) - Hatae, Ryusuke; Hata, Nobuhiro; Suzuki, Satoshi O.; Yoshimoto, Koji; Kuga, Daisuke; Murata, Hideki; Akagi, Yojiro; Sangatsuda, Yuhei; Iwaki, Toru; Mizoguchi, Masahiro; Iihara, Koji
Abstract : Brain tumors harbor various BRAF alterations, the vast majority of which are the BRAF kinase‐activating V600E mutation. BRAF mutations are most frequently detected in certain subtypes of low‐grade glioma, such as pilocytic astrocytoma (PA), pleomorphic xanthoastrocytoma (PXA), ganglioglioma (GG) and dysembryoplastic neuroepithelial tumor (DNT). However, it is unclear whether gliomas harboring BRAF mutations can be invariably regarded as these glioma subtypes or their derivatives. To address this question, we analyzed 274 gliomas in our institutional case series. We performed high‐resolution melting analyses and subsequent direct Sanger sequencing on DNA isolated from snap‐frozen tumor tissues. As expected, BRAF mutations were detected in the aforementioned low‐grade gliomas: in 4/27 PAs, 2/3 PXAs, 4/8 GGs, and 1/6 DNTs. In addition to these gliomas, 1/2 astroblastomas (ABs) and 2/122 glioblastomas (GBs) harbored BRAF mutations. Pathological investigation of the two GBs revealed that one was a GB displaying epithelial features that presumably arose from a precedent GG, whereas the other GB, which harbored a rare G596 A mutation, showed marked epithelial features, including astroblastic rosettes. Our results indicate that in addition to being present in established BRAF ‐associated gliomas, BRAF mutations might be associated with epithelial features in high‐grade gliomas, including sheet‐like arrangement of polygonal tumor cells with a plump cytoplasm and astroblastic rosettes, and thus could potentially serve as a genetic marker for these features.